Association of Brachial-Ankle pulse pressure with coronary artery stenosis severity: A sex-specific cross-sectional study in Chinese adults - Junnan Song; Haiyan Wang; Yali Mao; Lin Zheng; Lili Chen; Chunhui Yang; Zhongsu Shi; Huan Liu; Annuo Liu (PLoS ONE, 2026)
Objectives To investigate the association between brachial and ankle pulse pressure and the severity of coronary artery stenosis, as well as to explore sex-specific differences in these associations. Methods A total of 218 patients who attended a tertiary hospital in China from 1 July 2023–31 January 2024 were selected for the study. The brachial artery pulse pressure, ankle artery pulse pressure, degree of coronary artery stenosis, and the number of major vascular lesion branches were standardized and measured. Multiple logistic regression and receiver operating characteristic curves were employed for analysis. Results Pulse pressure values at all four measurement sites (left and right brachial, left and right ankle) were significantly higher in the severe coronary stenosis group (T3) compared with the mild stenosis group (T1; all P < 0.001). Multivariate logistic regression analysis showed that left brachial pulse pressure (LPP) was independently associated with severe coronary stenosis (OR: 0.048, 95% CI: 0.010–0.227, P = 0.01). ROC analysis revealed that LPP had favorable predictive performance for severe coronary stenosis, with AUC values of 0.862 in men and 0.854 in women. Gender differences were observed in ankle pulse pressure: right ankle PP showed numerically higher AUC values in men (0.847), while left ankle PP showed numerically higher AUC values in women (0.842). Conclusion Depending on gender and the patient’s specific condition, brachial and ankle pulse pressure are critical in assessing coronary stenosis. Site-specific pulse pressure measurements may help identify patients at higher risk of coronary stenosis, enabling effective interventions to better safeguard their cardiovascular health.